2013
DOI: 10.3346/jkms.2013.28.1.106
|View full text |Cite
|
Sign up to set email alerts
|

Growth after Hematopoietic Stem Cell Transplantation in Children with Acute Myeloid Leukemia

Abstract: Previous studies have shown that hematopoietic stem cell transplantation (HSCT) may result in growth impairment. The purpose of this study was to evaluate the growth during 5 yr after HSCT and to determine factors that influence final adult height (FAH). We retrospectively reviewed the medical records of acute myeloid leukemia (AML) patients who received HSCT. Among a total of 37 eligible patients, we selected 24 patients who began puberty at 5 yr after HSCT (Group 1) and 19 patients who reached FAH without re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Long‐term follow‐up also showed endocrine complications (hypogonadisms and delayed growth) following surgical and chemotherapy treatment of high‐risk neuroblastomas in 28% of children 82 . Catch‐up growth can occur during times of remission following treatment for cancer in patients without a history of radiation therapy 83 . GH therapy may improve growth in children with growth failure after irradiation for brain tumors 84 .…”
Section: Cancermentioning
confidence: 99%
“…Long‐term follow‐up also showed endocrine complications (hypogonadisms and delayed growth) following surgical and chemotherapy treatment of high‐risk neuroblastomas in 28% of children 82 . Catch‐up growth can occur during times of remission following treatment for cancer in patients without a history of radiation therapy 83 . GH therapy may improve growth in children with growth failure after irradiation for brain tumors 84 .…”
Section: Cancermentioning
confidence: 99%
“…Those who did not receive radiotherapy but had a chronic GVHD diagnosis showed a decreasing height z score only up to the 5-year posttransplant mark. 25 Rodgers et al 26 performed a broader study involving additional anthropometric measures on pediatric patients who received allogeneic HSCT, and identified that weight, skinfold measurements, and midupper arm circumference (MUAC) measurements in this population remained lower than their measurements taken pretransplant. These findings were supported by Hoffmeister et al, 27 who reported that arm anthropometric measures including MUAC were better predictors of pediatric patient outcomes in allogeneic HSCT (including event-free survival, acute, and chronic GVHD) than BMI.…”
Section: Nutrition Diagnosis and Evaluation Of Anthropometricsmentioning
confidence: 99%
“…Finally, the authors identified that those patients who received radiotherapy and were diagnosed with chronic GVHD post‐HSCT had height Z scores that continued to decrease even 5 years posttransplant. Those who did not receive radiotherapy but had a chronic GVHD diagnosis showed a decreasing height z score only up to the 5‐year posttransplant mark 25 . Rodgers et al 26 performed a broader study involving additional anthropometric measures on pediatric patients who received allogeneic HSCT, and identified that weight, skinfold measurements, and midupper arm circumference (MUAC) measurements in this population remained lower than their measurements taken pretransplant.…”
Section: Mnt: Screening Nutrition Assessment and Determination Of Mnt...mentioning
confidence: 99%
“…Young age at irradiation and the absence of dose fractionation in TBI are predictive of growth hormone (GH) deficiency and growth retardation in 20-50% of the patients having received brain irradition or TBI in addition to chemotherapy. This deficiency results in small adult height stature, which may also be favored by skeletal anomalies and gonadal failure [ 29 , 30 ].…”
Section: Endocrine Complicationsmentioning
confidence: 99%
“…As described above, low oestrogen or testosterone levels and non-elevated gonadotropins levels are suggestive of gonadotropin deficiency that is amenable to hormone replacement therapy [ 29 , 30 ].…”
Section: Endocrine Complicationsmentioning
confidence: 99%